Evolution and Adaptation of Large Language Models for Bahasa Indonesia - Allan Desi Alexander; Siti Setiawati (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2026)
This study evaluates the systematic evolution and computational adaptation of pre-trained language models and Large Language Models (LLMs) for Bahasa Indonesia and its low-resource regional dialects. Initially centered on bidirectional encoder-based representations like IndoBERT, the regional natural language processing (NLP) field has transitioned toward generative sequence-to-sequence structures and massive decoder-only architectures. This paper investigates the engineering methodologies of cross-lingual vocabulary adaptation, parameter initialization heuristics, and language-adaptive pre-training strategies designed to address text overfragmentation, representational misalignment, and tokenization cost inefficiencies. Through extensive structural benchmarks, this analysis compares discriminative and generative performances across tasks including sentiment classification, extractive question answering, text style normalization, domain-specific retrieval-augmented pipelines, and entity linking. While localized generative models such as Komodo, Sailor, and the SEA-LION suite improve contextual reasoning, colloquial style transfers, and regional dialect preservation, they remain susceptible to architectural anomalies like template leakage and entity hallucination. This study provides foundational benchmarks and methodological frameworks for adapting massive language models to morphologically rich, culturally diverse, and low-resource linguistic environments.